2008
DOI: 10.1158/0008-5472.can-08-2195
|View full text |Cite
|
Sign up to set email alerts
|

Lowering Bone Mineral Affinity of Bisphosphonates as a Therapeutic Strategy to Optimize Skeletal Tumor Growth InhibitionIn vivo

Abstract: Bisphosphonates bind avidly to bone mineral and are potent inhibitors of osteoclast-mediated bone destruction. They also exhibit antitumor activity in vitro. Here, we used a mouse model of human breast cancer bone metastasis to examine the effects of risedronate and NE-10790, a phosphonocarboxylate analogue of the bisphosphonate risedronate, on osteolysis and tumor growth. Osteolysis was measured by radiography and histomorphometry. Tumor burden was measured by fluorescence imaging and histomorphometry. NE-107… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
29
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 27 publications
2
29
2
Order By: Relevance
“…Incidentally, it has been reported that a carboxylate analog of Ris (with a P-C-COOH structure instead of P-C-P) reduces experimental bone-resorption in vitro, although its activity is 8000-fold less potent than that of Ris itself. 38,39) Thus, it also remains to be clarified whether such analogs can exert anti-bone-resorptive effects in vivo.…”
Section: )mentioning
confidence: 99%
“…Incidentally, it has been reported that a carboxylate analog of Ris (with a P-C-COOH structure instead of P-C-P) reduces experimental bone-resorption in vitro, although its activity is 8000-fold less potent than that of Ris itself. 38,39) Thus, it also remains to be clarified whether such analogs can exert anti-bone-resorptive effects in vivo.…”
Section: )mentioning
confidence: 99%
“…14 Risedronate, a potent antiosteolytic bisphosphonate used in the treatment of osteoporosis and Paget's disease, and its phosphonocarboxylate derivative NE-10790 has been recently tested for their therapeutic potential against bone cancers in mice. 15 The hypothesis for the study was that the lower bone affinity of NE-10790 would lead to it being more easily released from the bone surface and thereby increasing the tumor exposure to the compound. In fact, the article showed that risedronate reduced both bone degradation and tumor burden, whereas NE-10790 only led to a decrease in tumor burden without affecting bone degradation.…”
mentioning
confidence: 99%
“…In fact, the article showed that risedronate reduced both bone degradation and tumor burden, whereas NE-10790 only led to a decrease in tumor burden without affecting bone degradation. 15 On the basis of these results, we decided to investigate the effect of risedronate and NE-10790 on pain-related behavior in mice suffering from bone cancer. The individual contribution of osteoclast activity and tumor growth to bone cancer pain is poorly defined, because of their intermingled mechanisms, 6 and comparing the effect of risedronate and NE-10790 could further elucidate the importance of tumor burden for bone cancer pain.…”
mentioning
confidence: 99%
“…Therefore, for the adequate management of established metastatic disease in bone, bisphosphonates may have to be combined with other agents which specifically affect tumour growth and progression. Previous studies with bisphosphonates in combination with antitumor drugs were effective in decreasing tumour growth in relevant animal models and in vitro evidence of a synergism has been reported [34][35][36][37]. The question, therefore, addressed in this study was whether the combination of a bisphosphonate with a dose of a chemotherapeutic that has no effect on tumour growth when given alone, might act synergistically on tumour growth in vivo.…”
Section: Discussionmentioning
confidence: 98%
“…Bisphosphonates are cleared rapidly from the circulation and are taken up preferentially by the skeleton at active remodelling sites where they bind strongly to bone [32,33]. This action allows only very limited, if any, exposure of the cancer cells in the marrow to bisphosphonates [34]. Therefore, for the adequate management of established metastatic disease in bone, bisphosphonates may have to be combined with other agents which specifically affect tumour growth and progression.…”
Section: Discussionmentioning
confidence: 99%